Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/horticulturae7070188
|View full text |Cite
|
Sign up to set email alerts
|

Application of Room Cooling and Thermal Insulation Materials to Maintain Quality of Okra during Storage and Transportation

Abstract: A combination of room cooling and the use of thermal insulation materials to maintain okra quality under simulated storage and transportation was evaluated. Okra pods were packed in plastic baskets and either cooled at 18 °C or not cooled in a room for 2 h. After either room cooling or no cooling, the okra pods were covered with three different materials: (1) perforated linear low-density polyethylene (P-LLDPE), (2) two layers of heat-reflective sheet with thin nonwoven (HRS+TNNW), and (3) metalized foam sheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
5
6
0
Order By: Relevance
“…The use of thermal insulation covers containing aluminum sheet (HRS + TNNW, HRS + TKNW and MFS) over 7 h resulted in greater heat accumulation inside the cover, caused by the high respiration of okra compared with no cover and P-LLDPE treatments (Figures 5-7). Similarly, our previous study showed that thermal insulation materials (HRS + TNNW and MFS) tended to build up pulp temperature of okra under simulated transportation at 30 • C for 15 h [16]. This result was consistent with Bycroft et al [42] who recommended that long-term covering of asparagus should be reconsidered due to higher heat accumulation compared to no cover.…”
Section: Temperature and Relative Humidity Inside Cover Materialssupporting
confidence: 87%
See 4 more Smart Citations
“…The use of thermal insulation covers containing aluminum sheet (HRS + TNNW, HRS + TKNW and MFS) over 7 h resulted in greater heat accumulation inside the cover, caused by the high respiration of okra compared with no cover and P-LLDPE treatments (Figures 5-7). Similarly, our previous study showed that thermal insulation materials (HRS + TNNW and MFS) tended to build up pulp temperature of okra under simulated transportation at 30 • C for 15 h [16]. This result was consistent with Bycroft et al [42] who recommended that long-term covering of asparagus should be reconsidered due to higher heat accumulation compared to no cover.…”
Section: Temperature and Relative Humidity Inside Cover Materialssupporting
confidence: 87%
“…Equipment settings and thermal heat energy measurements were performed following the procedure of Harvey [25] and our previous research [16]. Briefly, rate of thermal heat energy (Q x ) was determined as the rate at which heat energy passed through the material by using two expanded polystyrene (EPS) boxes with a hole (10 × 10 cm 2 ) between two chambers.…”
Section: Determination Of Materials Propertiesmentioning
confidence: 99%
See 3 more Smart Citations